Reformulating Tax Dispute Regulations as an Effort to Address Substantive Injustice in Indonesia's Tax Court System - Ryandi Ferdiannur Usman; Prija Djatmika; Heru R. Hadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study examines the urgency of reformulating tax dispute resolution regulations in Indonesia to address the substantive injustice experienced by taxpayers within the tax judiciary system. Although Indonesia's taxation system is founded on the principle of legality under Article 23A of the 1945 Constitution, the existing dispute resolution mechanism has not fully ensured balanced legal protection between taxpayers and tax authorities. Tax authorities possess extensive powers in tax assessment, examination, and collection, creating an unequal position that may lead to unfair treatment of taxpayers. This research aims to analyze the current legal framework governing tax dispute resolution and identify the factors contributing to substantive injustice in the system. The study employs a normative juridical method using statutory and conceptual approaches through the examination of relevant legislation, legal principles, and legal doctrines. The findings indicate that tax disputes are primarily resolved through appeals and lawsuits under the jurisdiction of the Tax Court, while objections constitute an administrative remedy within the broader tax dispute framework. However, taxpayers continue to face significant challenges, including potential conflicts of interest in the objection process, unequal burdens of proof, limited access to information, and regulatory inconsistencies among the General Taxation Provisions and Procedures Law, the Tax Court Law, and the Judicial Power Law. These conditions weaken legal protection and hinder the realization of substantive justice. This study recommends a comprehensive reformulation of tax dispute regulations to strengthen the independence of the Tax Court, improve legal protection for taxpayers, and promote substantive justice within Indonesia's tax dispute resolution system. Such reform is expected to enhance legal certainty, fairness, and public trust in the national taxation system.. This study fills the research gap concerning the limited discussion of substantive justice in Indonesian tax adjudication and proposes an original reformulation model emphasizing independent review, broader judicial scrutiny, and stronger taxpayer protection.